Sn-Doped Bi2O3 nanosheets for highly efficient electrochemical CO2 reduction toward formate production. Issue 46 (24th November 2021) - Li, Xiao; Wu, Xingqiao; Li, Junjie; Huang, Jingbo; Ji, Liang; Leng, Zihan; Qian, Ningkang; Yang, Deren; Zhang, Hui
Abstract : Sn-Doped Bi2 O3 nanosheets showed enhanced catalytic selectivity and activity for CO2 RR relative to undoped ones with 2.5% Sn-doped Bi2 O3 NSs showing a highest FE of over 93% and a largest current density of nearly 50 mA cm −2 for formate in H-cell. Abstract : Electrocatalytic CO2 reduction to formate is considered as a perfect route for efficient conversion of the greenhouse gas CO2 to value-added chemicals. However, it still remains a huge challenge to design a catalyst with both high catalytic activity and selectivity for target products. Here we report a unique Sn-doped Bi2 O3 nanosheet (NS) electrocatalyst with different atomic percentages of Sn (1.2, 2.5, and 3.8%) prepared by a simple solvothermal method for highly efficient electrochemical reduction of CO2 to formate. Of them, the 2.5% Sn-doped Bi2 O3 NSs exhibited the highest faradaic efficiency (FE) of 93.4% with a current density of 24.3 mA cm −2 for formate at −0.97 V in the H-cell and a maximum current density of nearly 50 mA cm −2 was achieved at −1.27 V. The formate FE is stable maintained at over 90% in a wide potential range from −0.87 V to −1.17 V. Electrochemical and density functional theory (DFT) analyses of undoped and Sn doped Bi2 O3 NSs indicated that the strong synergistic effect between Sn and Bi is responsible for the enhancement in the adsorption capacity of the OCHO* intermediate, and thus the activity for formate production. In addition, we coupled 2.5% Sn-doped Bi2 O3 NSs with a dimensionally stable anode (DSA) to realize battery-driven highly active CO2 RR and OER with decent activity and efficiency.